OVERCOMING THE CHALLENGE OF ANTIBIOTIC RESISTANCE AND IMPROVING GLOBAL HEALTH THROUGH TELEMEDICINE AND INNOVATIONS (KIUT Publication, 2025)
According to the World Health Organization (WHO), every year more than 700,000 people die due to antibiotic-resistant infections. By 2050, this number is projected to reach 10 million. This poses a significant threat not only to healthcare but also to the socio-economic well-being of the global community. Antibiotic resistance negatively affects the reliability of healthcare systems, the duration of disease treatment, and healthcare-related expenses.